2017
DOI: 10.1149/2.1411712jes
|View full text |Cite
|
Sign up to set email alerts
|

State of Charge and State of Health Estimation Using Electrochemical Acoustic Time of Flight Analysis

Abstract: Ultrasonic analysis was used to predict the state of charge and state of health of lithium-ion pouch cells that have been cycled for several hundred cycles. The repeatable ultrasonic trends are reduced to two key metrics: time of flight shift and total signal amplitude, which are then used with voltage data in a supervised machine learning technique to build a model for state of charge (SOC) prediction. Using this model, cell SOC is predicted to ∼1% accuracy for both lithium cobalt oxide and lithium iron phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 26 publications
3
103
0
Order By: Relevance
“…Figure 3c shows that the TOF basically increases as the battery degrades. Increasing of TOF indicates decreasing of the ultrasound velocity, which is a result of the changes in the electrode densities and modulus (i.e., the lithium content changes in each electrode) as a battery degrades [28,31]. Note that an increase of TOF could also indicate an increase in the thickness.…”
Section: Ultrasonic Results For the Cycling Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3c shows that the TOF basically increases as the battery degrades. Increasing of TOF indicates decreasing of the ultrasound velocity, which is a result of the changes in the electrode densities and modulus (i.e., the lithium content changes in each electrode) as a battery degrades [28,31]. Note that an increase of TOF could also indicate an increase in the thickness.…”
Section: Ultrasonic Results For the Cycling Testsmentioning
confidence: 99%
“…Note that an increase of TOF could also indicate an increase in the thickness. However, changes of thickness are ignored in this case as they are not the main contributor to TOF changes according to [28]. In addition, the signal amplitude, in Figure 3c, generally increases before cycle 50, followed by a fluctuation after cycle 50.…”
Section: Ultrasonic Results For the Cycling Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that VRFB electrolyte conductivity is highly dependent on temperature, and errors can happen because of side reactions. It was also observed that ultrasonic waves propagate through the electrolytes with distinctly different velocities according to different vanadium ion compositions [10,11]. Open-circuit voltage (OCV) measurement was used to estimate VRFB's SOC in [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to SOC, state-of-health (SOH) of the battery also needs to be monitored by BMS. 52 The SOH demonstrates a battery energy storage and delivery capability compared to its original condition. When the battery is fresh, SOH equals to 100% and decreases as the battery ages.…”
mentioning
confidence: 99%